A quantum chemical investigation of potential applicability of X12Y12 (X= B, Al, C; Y= N, P, C) nanocages for efficient removal of levofloxacin through water - Aydogdu, Seyda (ELSEVIER SCIENCE INC, 2026)
In the last years, growing human populations and economies have led to increasing environmental pollution, especially in water. Due to the adverse effects of antibiotics in the water environment, public concerns have increased about the health issue. For this reason, removal of antibiotic pollutants from the water environment is urgently needed. This work has been conducted in order to find a suitable adsorbent nanocage structure from X12Y12 (B12N12, Al12N12, B12P12, Al12P12, C24) for removing levofloxacin antibiotic by using Density Functional Theory. The favorable adsorption processes are determined via adsorption energies and thermodynamic results for various orientations of levofloxacin onto the nanocages. The electronic nature of the adsorption processes is investigated with the help of Mulliken analysis, Natural Bond Orbital Analysis, and Quantum Theory of Atoms in Molecules. The reactivity and sensitivity investigation of the nanocage and levofloxacin complex systems is elucidated with global reactivity indices, Frontier Molecular Orbitals, Density of States spectra, and work function. The change of dipole moment values after adsorption are determined. The spontaneous characters of adsorption processes are determined. Furthermore, the number of LEV molecules, the water medium and the saline content of water effects the adsorption of LEV have been determined. The outcomes of this study demonstrate that Al12N12 and Al12P12 nanocages can be useable for effective removal of levofloxacin. The results of this study will be a novel contribution for further studies in order to remove levofloxacin effectively.
Keywords: Adsorption; Antibiotic; Density functional theory; Levofloxacin; Nanocage; Water; OPTIMIZATION; DEGRADATION; OXIDATION; MECHANISM; BEHAVIOR; ATOMS; Biochemistry & Molecular Biology; Computer Science; Crystallography; Mathematical & Computational Biology